Предмет: Математика,
автор: natashamun94
Помогите с решением
Упростить выражение : cos(6п - а) + cos(п + а) +1
Ответы
Автор ответа:
0
Воспользуемся формулами приведения:
cos(6п - а)=cos(-a)=cosa
cos(п + а)=-cosa
cos(6п - а) + cos(п + а) +1=cosa-cosa+1=1
cos(6п - а)=cos(-a)=cosa
cos(п + а)=-cosa
cos(6п - а) + cos(п + а) +1=cosa-cosa+1=1
Автор ответа:
0
Похожие вопросы
Предмет: Информатика,
автор: Аноним
Предмет: Математика,
автор: lidakraw02
Предмет: Українська мова,
автор: Tiger109
Предмет: Физика,
автор: alecsandra97